Acid Exchanged Montmorillonite Catalyzed Condensation Reaction of Fluoroalkyliodide onto Amines - Hachemaoui, Aicha; Belbachir, Mohammed; Yahiaoui, Ahmed (Asian Journal of Chemistry, 2016)
The H-maghnite (Maghina, Algeria), a monthmorillonite sheet silicate clay was treated in different H2SO4 concentrations at 20ºC. The aluminum and silicon were identified by 27Al and 29Si MAS NMR spectroscopy. Three different types of structural units were identified in acid-treated maghnite Q4(0A1) units of amorphous silica with three-dimensional cross-liked framework; (SiO)3SiOH and Q4(1A1) units. The catalytic activity of acid-treated maghnite was evaluated by reacting 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluoro-8-iodo octane with several amines to yield perfluoroalkylamines and no byproducts were obtained during the reaction. The structure of perfluoroalkylamines obtained during the reaction. The structure of perfluoroalkylamines obtained was characterized by 1H, 13C and 19F NMR.